Partial Budget Analysis and Consumer Response to Hydroponic Vegetable Packaging Innovation (Study at CV. AMATTA MULYA BARIZI) - Rafif Ikhsan Mahadhika; Kuswarini Sulandjari; Ekalia Yusiana (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose: This study analyzes the differences in partial budgeting and added value between old and new packaging on company revenue and evaluates consumer responses to the new packaging by CV. Amatta Mulya Barizi. Methodology: A quantitative method with 100 respondents selected through incidental sampling. Data were obtained via interviews and observations. Analysis involved partial budgeting and descriptive analysis using a Likert scale. Results: Partial budgeting analysis showed changes in costs, with an additional packaging cost of Rp 300 and additional revenue of Rp 800. The new packaging added value to the company's revenue by 1.67, indicating that each Rp 1.00 spent on new packaging generated Rp 1.67 in revenue. Findings: Consumer responses to the packaging function were high, with a score index of 76.93%. The competitive advantage response scored 70.95%, and consumer satisfaction scored 77.80%. Overall, consumer response to the new packaging was high, with an index of 76.08%. Novelty: This research provides insights into the financial impact and consumer acceptance of packaging innovation in hydroponic vegetable production. Originality: The study offers a detailed analysis of the economic benefits and consumer perceptions of new packaging, enhancing understanding of its role in product marketing. Conclusions: The new packaging innovation positively impacts the company's revenue and is well-received by consumers, benefiting CV. Amatta Mulya Barizi. Type of Paper: Empirical Research Article